Handbook on Corporate Governance in Financial Institutions 2016
DOI: 10.4337/9781784711795.00019
|View full text |Cite
|
Sign up to set email alerts
|

Corporate governance practices in the Nigerian banking industry

Abstract: Corporate governance is particularly of importance in the Nigeria banking industry where a number of financial failures and questionable business practices had negatively impinged investors" confidence.This study examined corporate governance practices in Nigerian banks with regards to board characteristics, performance, culture and processes, and impact on board effectiveness. It also attempted to identify the level of compliance of Nigerian banks to the Central Bank of Nigeria (CBN) code of corporate governa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 12 publications
0
14
0
Order By: Relevance
“…Non-executive directors are outside directors who are independent of the company. According to the study [39] Ogbechie and Koufopoulos, (2010), non-executive directors are referred to as independent directors because they have neither personal nor business relationships with the company. This means that non-executive is any director who is not a representative or member of the immediate family of a shareholder and who has no business relationship with the company but seats on the management board to help check the excesses that may arise from the executive directors.…”
Section: Independent/non-executive Directorsmentioning
confidence: 99%
“…Non-executive directors are outside directors who are independent of the company. According to the study [39] Ogbechie and Koufopoulos, (2010), non-executive directors are referred to as independent directors because they have neither personal nor business relationships with the company. This means that non-executive is any director who is not a representative or member of the immediate family of a shareholder and who has no business relationship with the company but seats on the management board to help check the excesses that may arise from the executive directors.…”
Section: Independent/non-executive Directorsmentioning
confidence: 99%
“…Board size refers to the total number of directors on the board of any corporate organization (Dozie, 2003;Ogbechie and Koufopoulos, 2010:6). Determining the ideal board size for an organization is very important because the number and quality of directors in a firm determine and influence the board functioning and corporate profitability (Ogbechie and Koufopoulos, 2010). Dabor, et al (2015), posit that there is no agreed number of members that make up an ideal board size.…”
Section: Board Sizementioning
confidence: 99%
“…It means the ability to conduct board activities for which a director was trained and inducted as prescribed in the code of corporate governance. According to Ogbechie and Koufopoulos (2010), the knowledge and skills most relevant to boards are in two dimensions: functional area knowledge and skills and firm-specific knowledge and skills. According to them, functional area knowledge and skills include accounting, finance, marketing, and law.…”
Section: Board Skills and Competencementioning
confidence: 99%
“…There are no regulators reports on the level of compliance of corporate governance code except for those of individual researchers. In a study by Ogbechie and Koufopoulos [36], titled 'corporate governance and Board practices in the Nigeria banking industry', they reported that Nigerian banks have a high degree of compliance with the Central Bank of Nigeria code of corporate governance. Conversely, Onakoya, Ofoegbu and Fasanya [18] showed a low compliance rate by the banks listed on the Nigerian Stock Exchange.…”
Section: Independent Oversight and Enforcementmentioning
confidence: 99%